PERAN AMERIKA SERIKAT DALAM MENCIPTAKAN PERDAMAIAN DAN PENYELESAIAN KONFLIK ISRAEL DAN PALESTINA - Rahmatullah, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2015)
The early occurrence of the Palestinian conflict – Israel is after the defeat of the Ottoman Empire Turkey from United Kingdom and its allies; America, France and Russia in 1916, and continued with the wishes of Foreign Minister Arthur James Balfour, known as the Balfour Declaration, on November 2, 1917. The purpose of this research is to provide an overview, description and understanding of the occurrence of events of the conflict in the Palestinian territories, by looking at the origins of the conflict, the role of actors who play the political scene so that the occurrence of disputes in Palestine-Israel and the participation of United Nations agencies in the resolution of the conflict in the Middle East. The method used is descriptive approach to techniques of gathering facts through sorcery, libraries in the form of qualitative and quantitative studies. The results of the study are: (1) the Government of Israel led by Prime Minister Benjamin Netanyahu no intention to resolve conflicts in both Israel military forces with Palestinian Military, (2) the role of the United Nations as an institution – the peace of the world, does not give a significant influence in the eyes of the Government of Benjamin Netanyahu-Israel, (3) the presence of large United States against Israel's interests in terms of business and armament of the Suez Canal in the Palestinian territories, (4) United States cannot stop Israel military offensive action to the Palestinian territories, as it has the national interest of the State of Palestine, (5) the Foundation of Israel as a means of committing military aggression in order to smoothen the supply of weaponry as well as keepers of the Suez Canal.